The Use of Al-Jaldah (الجلدة) And Ad-Ḍarbah (الضربة) As A Method of Spiritual Healing An Analysis From Islamic Medical Practice - Mahyuddin, Ismail (Universitas Islam Raden Rahmat Malang, 2023)
Islamic medical practice employs a variety of techniques and approaches. Some have been well established and widely practiced, and some are not yet being explored and understood in depth. The use of Al-Jaldah (الجلدة) and Ad-Ḍarbah (الضربة) in treating patient is rarely discussed. It raises the question whether such practice has basis in Islam. This study aims to examine whether such treatment complies with Islamic teachings or not. The methodology applied is purely qualitative as it involves cross-field studies in Sharia and Islamic medical practice. The information was gathered through library research and interview with practitioner of the technique. The findings of this study are: (i) Al-Jaldah (الجلدة) and Ad-Ḍarbah (الضربة)as a form of treatment have their roots in the Al-Quran, Al-Hadith and practice of prominent Muslim scholars (Spiritual Healingin Islam); (ii) despite its sound fundamental, such treatment must adhere to a set of care guidelines. The findings of this study will resolve any issue surrounding the subject of such treatment. This study will also assist the relevant authorities in addressing current concerns that call for in-depth research.